Impacted tooth brush in retromolar area: a practical management of difficult airway - Deo, Gopendra Prasad; Majhi, Prakash Chandra (Journal of Society of Anesthesiologists of Nepal, 2015)
Proper airway management is an important skill for an Anaesthesiologist. This case report deals with airway management performed in a forty five years lady, with impacted tooth brush in the retromolar region on the right side. She was intubated and the foreign body was removed surgically without any peri-operative complications. This case report discusses the complications and management of oropharyngeal injuries by stick-like foreign bodies such as a toothbrush or a chopstick. The article also focuses on basic airway management and some tracheal intubation techniques that may be performed to solve a difficult airway. Journal of Society of Anesthesiologists 2014 1(1): 51-54